Factors associated with use of antibiotic prophylaxis following dental procedures in total joint replacement recipients. Issue 4 (December 2021) - Katz, Jeffrey N.; Song, Zoey S.; Stanley, Elizabeth E.; Lenhard, Nora K.; Silva, Genevieve S.; Chen, Angela; Thornhill, Thomas S.; Lange, Jeffrey; Collins, Jamie E.; Selzer, Faith; Losina, Elena
Abstract: Background: Total joint replacement recipients (TJR) are at risk for prosthetic joint infection (PJI), particularly those with comorbidities such as diabetes mellitus (DM) and rheumatoid arthritis (RA). Methods: We mailed surveys to 1078 subjects undergoing primary TJR between 2011 and 2016 ​at an academic center. The survey asked about medical, dental, and orthopedic history and use of antibiotics prior to dental appointments. We generated adjusted relative risks (aRR) for using antibiotic prophylaxis less than always using Poisson regression, adjusting for demographic, clinical, and behavioral factors. Results: We received surveys from 639 subjects; 597 were eligible and formed the analytical sample. 66 ​% reported always using antibiotic prophylaxis. DM and RA were not associated with prophylaxis use. Factors associated with less frequent use included: BMI ≥30 (aRR ​= ​1.27, 95 ​% CI [1.01, 1.60]), dental cleanings <2 times/year (aRR ​= ​1.95, 95 ​% CI [1.56, 2.43]), and expressing little concern (compared to neutral) about getting PJI (aRR ​= ​1.23, 95 ​% CI [0.97, 1.55]), though this association was not statistically significant. Greater antibiotic use was reported in subjects who had ≥3 TJRs, (aRR ​= ​0.48, 95 ​% CI [0.29, 0.80]), underwent more invasive dental procedures (aRR ​= ​0.74, 95 ​% CI [0.59, 0.93]), and were concerned (vs. neutral) about PJI (aRR ​= ​0.53, 95 ​%CI [0.33, 0.84]). Conclusions: Two-thirds of TJR recipients in an academic center reported always using antibiotic prophylaxis prior to dental visits. Usage rates varied by demographics, BMI, number of TJRs, type of dental procedure, and behavioral factors – but not by comorbidities associated with higher PJI risk.